Basic concepts, engineering, and advances in dye-sensitized solar cells - Mathpal, Mohan Chandra (2020)
The day–by-day increasing need for light energy has reduced the necessary supply of energy for mankind usage and hiked the prices of natural energy resources. To avoid energy tragedy in future, one needs to use the non-degrading sources of energy for energy harvesting. The advancement in solar cell technology allows us to convert the sunlight more efficiently into electrical energy, though the low cost with highly stable and efficient solar cells is still desirable. The dye-sensitized solar cells (DSSCs), a class of third-generation photovoltaic cell, have emerged out as economic, eco-friendly, and much easier fabrication process over other existing technologies such as single-crystal Si solar cells, polycrystalline Si solar cells, thin-film solar cells, and other semiconductor (GaAs, CdTe, CuInSe2, etc.) thin films. The main challenge and limiting factor with DSSC’s fabrication are their efficiency and durability in the environment. In the last decade, enormous efforts have been made to improve the efficiency and stability of DSSCs. One of the possible ways is the manipulation of light at nanoscale on some metal–dielectric interface and integrating it on some cheaper electronic devices for highly efficient solar cell applications. On the other hand, the research on modifying the design and fabrication of photoanode, dyes materials, and counter electrode materials have paid huge attention in architecting DSSCs. This chapter provides an insight into the fabrication of DSSCs and the challenges associated with its fabrication, stability, and efficiency.